Are mental toughness and mental health contradictory concepts in elite sport? A narrative review of theory and evidence. Issue 3 (March 2017) - Gucciardi, Daniel F.; Hanton, Sheldon; Fleming, Scott
Abstract: Objective: Athlete development and management encompass a complex interaction of biological, psychological, and social factors. Within elite sport, multidisciplinary sport science and medicine teams play an important role in achieving an optimal balance between preventing athlete ill-health and optimizing health and performance. The psychological aspects of athlete health and performance have gained increased attention over the past two decades, with much of this research concerned with the mental health of athletes and the concept of mental toughness. Recently, it was proposed that mental health and mental toughness are contradictory concepts in the world of elite sport. Although an interesting proposition, this claim was not substantiated. Thus, the purpose of this narrative review was to evaluate theory and evidence regarding the thesis that mental health and mental toughness are contradictory concepts in the world of elite sport, with the view to advance scholarly knowledge and inform professional practice. Design: Narrative review. Results: A critical evaluation of this literature suggests that mental toughness may represent a positive indicator of mental health, or facilitate its attainment, rather than be at odds with it. Conclusion: When implemented alongside multilayered approaches to organizational change (e.g., group structures, policies), mental toughness could be used as a 'hook' to attract athletes into settings that can open dialogue on the importance of mental health and improve knowledge of key issues (e.g., stigma, symptoms).